2014
DOI: 10.1121/1.4890643
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic characterization of monodisperse lipid-coated microbubbles: Relationship between size and shell viscoelastic properties

Abstract: The acoustic attenuation spectrum of lipid-coated microbubble suspensions was measured in order to characterize the linear acoustic behavior of ultrasound contrast agents. For that purpose, microbubbles samples were generated with a very narrow size distribution by using microfluidics techniques. A performance as good as optical characterization techniques of single microbubbles was achieved using this method. Compared to polydispersions (i.e., contrast agents used clinically), monodisperse contrast agents hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 36 publications
4
44
0
Order By: Relevance
“…HFBII Gibbs monolayers adsorbed at the air/water interface are known to exhibit ac oncentration-dependent transition from af luid to a2 D solid state,r esulting in high shear elasticity. [10] Finally,s ome feasibility tests showed that dispersing HFBII and preparing microbubbles using standard procedures leads to heterogeneous mixtures consisting largely of micron-sized aggregates along with both spherical and elongated microbubbles (see below), thus impeding the reproducible and effective formation of echogenic microbubbles. Another consequence of HFBII monolayers being in as olid state is that millimetric [8] and micrometric [9] HFBII-stabilized bubbles adopt elongated shapes.D ispersions containing both elongated and spherical microbubbles are suboptimal as USCAs ince microbubble resonance frequency depends on the radius.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HFBII Gibbs monolayers adsorbed at the air/water interface are known to exhibit ac oncentration-dependent transition from af luid to a2 D solid state,r esulting in high shear elasticity. [10] Finally,s ome feasibility tests showed that dispersing HFBII and preparing microbubbles using standard procedures leads to heterogeneous mixtures consisting largely of micron-sized aggregates along with both spherical and elongated microbubbles (see below), thus impeding the reproducible and effective formation of echogenic microbubbles. Another consequence of HFBII monolayers being in as olid state is that millimetric [8] and micrometric [9] HFBII-stabilized bubbles adopt elongated shapes.D ispersions containing both elongated and spherical microbubbles are suboptimal as USCAs ince microbubble resonance frequency depends on the radius.…”
mentioning
confidence: 99%
“…Another consequence of HFBII monolayers being in as olid state is that millimetric [8] and micrometric [9] HFBII-stabilized bubbles adopt elongated shapes.D ispersions containing both elongated and spherical microbubbles are suboptimal as USCAs ince microbubble resonance frequency depends on the radius. [10] Finally,s ome feasibility tests showed that dispersing HFBII and preparing microbubbles using standard procedures leads to heterogeneous mixtures consisting largely of micron-sized aggregates along with both spherical and elongated microbubbles (see below), thus impeding the reproducible and effective formation of echogenic microbubbles.…”
mentioning
confidence: 99%
“…To experimentally explore the pressure-dependent changes of the sound speed and attenuation for coated MBs, monodisperse lipid shell MBs were produced using flow-focusing in a microfluidic device as previously described [29,37]. Figure 2 shows the size distribution of the MBs in our experiments.…”
mentioning
confidence: 99%
“…Figure 2 shows the size distribution of the MBs in our experiments. The setup for the attenuation and sound speed measurements is the same as the one used in [37]. The thermal properties for the gas can be found in [38].…”
mentioning
confidence: 99%
“…Clinical ultrasound scanners operate at a narrow frequency bandwidth and as the resonance frequency of a bubble is directly related to its size 37 , only a small fraction of the UCA population resonates to the driving ultrasound field. The sensitivity increase that may result from the use of monodisperse UCA was already frequently suggested 4,64,65,118,[135][136][137] . In-vitro experiments have shown that the echo response of monodisperse bubbles presents a higher inter-echo correlation than that of a polydisperse population 4 .…”
Section: Introductionmentioning
confidence: 99%